Circulating Tumor Cells: Strategies for Capture, Analyses, and Propagation. Issue 2 (March 2018) - Agarwal, Ashutosh; Balic, Marija; El-Ashry, Dorraya; Cote, Richard J.
Abstract : Abstract: Circulating tumor cells (CTCs) play a central role in tumor dissemination and metastases, which are ultimately responsible for most cancer deaths. Technologies that allow for identification and enumeration of rare CTC from cancer patients' blood have already established CTC as an important clinical biomarker for cancer diagnosis and prognosis. Indeed, current efforts to robustly characterize CTC as well as the associated cells of the tumor microenvironment such as circulating cancer associated fibroblasts (cCAF), are poised to unmask key insights into the metastatic process. Ultimately, the clinical utility of CTC will be fully realized once CTC can be reliably cultured and proliferated as a biospecimen for precision management of cancer patients, and for discovery of novel therapeutics. In this review, we highlight the latest CTC capture and analyses technologies, and discuss in vitro strategies for culturing and propagating CTC.